Seismic Risk Management of Insurance Portfolio Using Catastrophe Bonds. (11th September 2014) - Goda, Katsuichiro; Iervolino, Iunio; Ellingwood, Bruce R.
Abstract Parametric earthquake catastrophe bonds are emerging risk transfer instruments for governments and insurers. This study extends a current station‐intensity‐based trigger method for binary payments, which utilizes direct observation of ground motions at recording stations, by promoting a more flexible multiple‐discrete payment structure. A calibration procedure of the bond trigger mechanism for the new approach is demonstrated by focusing upon a realistic portfolio of conventional wood‐frame houses in Vancouver, Canada. Numerical results indicate that the new method with a multiple‐discrete payment structure decreases the magnitude of trigger errors significantly in terms of seismic loss, and facilitates the flexible adoption of various payment structures for catastrophe bonds. Furthermore, a synergy between the calibration of parametric catastrophe bonds and the current performance‐based earthquake engineering framework is highlighted.